Dinâmicas de gênero no parlamento das águas: o caso do Comitê de bacia Rio Pardo (SP) - Souza, Janaina dos Santos de (Universidade Federal de São Carlos, 2022)
This work focused on analyzing the conflicts and dynamics of gender relations in the water parliament, more specifically in the management unit of the Rio Pardo Basin Committee (CBH-Pardo), which is a fundamental space in terms of the economy paulista, mainly due to sugarcane monoculture activities. Considering the participatory character proposed by this governance model, we seek to understand the participation of women in this management instance from its first management team, started in 1996, until the management of the year 2019, also highlighting the plenary with the right to vote. It is important to emphasize that this analysis did not take place only in terms of the number these women, but in the participatory quality and in the way of their insertion in the internal organizational structures of the committee. We work with the hypothesis that the governance structure of São Paulo waters, more specifically the CBH-Pardo, reproduces an organizational model that generates different types of conflicts and gender dynamics, which are the result of tensions of a power legitimized through of central forces in the field of technical-scientific knowledge and the market. A qualitative approach of social research was used in the research, through bibliographic research, survey and document analysis, as well as semi-structured and in-depth interviews with the participating members of the Committee. From this we can highlight two important results of the research carried out: the first one that is guided by a reorganization of our original hypothesis, showing that this space not only showed us models and gender conflicts, but also presented us with the democratic limits of the formation of the committee , which did not overcome traditional and social values; and the second one that properly refers to the scope of power relations and how these are placed in the path of a participatory parity look, outlining the central and peripheral relations that design the participation of these women .
Gender dynamics in the water parliament: the case of Pardo Rio basin Committee (SP)
Keywords: Relações de gênero; Poder; Gestão ambiental; Comitês de Bacia; Gender relations; Power; Environmental Management; Basin Committees; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL